Toxic effects of microcystin‐LR on the HepG2 cell line under hypoxic and normoxic conditions. Issue 10 (27th April 2012) - Zhang, Xin; Xie, Ping; Zhang, Xuezhen; Zhou, Wenshan; Zhao, Sujuan; Zhao, Yanyan; Cai, Yan
ABSTRACT: Microcystins (MCs) are highly liver‐specific and evidenced as a liver tumor promoter. Oxidative stress is one of the most important toxicity mechanisms of MCs, which is tightly related to oxygen concentration. The effects of MCs on animals and cell lines in normoxia and the mechanisms have been well studied, but such effects in different oxygen conditions were still unclear. The aim of the present study was to explore the cellular response of the human hepatocellular carcinoma cell line (HepG2) to MC‐LR exposure under hypoxic (1% O2 ) and normoxic (21% O2 ) conditions. We examined cell viability, mitochondrial membrane potential (MMP), superoxide dismutase (SOD) activity and gene expression posttoxin exposure. Cell viability was increased by MC‐LR in normoxia although decreased in hypoxia. MC‐LR markedly induced MMP loss under hypoxic condition but only slightly MMP loss under normoxic condition. SOD activity was significantly induced by MC‐LR in hypoxia, indicating prolonged oxidative stress. Inhibitory apoptosis protein (c‐IAP2) was significantly up‐regulated by MC‐LR under normoxic condition, suggesting that c‐IAP2 played an important role in the promotion of cell proliferation by MC‐LR. These results indicate that MC‐LR promotes cell proliferation under normoxic condition whereas induces cell apoptosis under hypoxic condition. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Microcystins (MCs) are highly liver‐specific and evidenced as a liver tumor promoter. Oxidative stress is one of the most important toxicity mechanisms of MCs, which is tightly related to oxygen concentration. The effects of MCs on animals and cell lines in normoxia and the mechanisms have been well studied, but such effects in different oxygen conditions were still unclear.